Understanding the Concept of Riba in Fiqh al-Muamalat: Challenges in the Modern Global Economic System - Mukhlis Mukhlis; Alam Tarlam (Ar-rayyan: Journal Of Islamic Education, 2025)
This study explores the concept of riba (usury) as understood within Fiqh al-Muamalat, the branch of Islamic jurisprudence that governs economic and financial transactions. Riba, which is strictly prohibited in Islamic law, presents ongoing challenges in the context of the modern global economic system that is largely interest-based. The paper aims to provide a clear understanding of the different types of riba, their historical and textual foundations in the Qur’an and Hadith, and how classical and contemporary Islamic scholars interpret them. It also examines the practical difficulties faced by Muslim-majority countries and Islamic financial institutions in aligning Shariah-compliant financial practices with global economic structures. The findings highlight the tension between religious doctrine and economic pragmatism, and suggest the need for innovative, ethically grounded financial solutions that uphold Islamic principles while engaging with the realities of the modern economy